P170 Potential role for the chemokine CCL22 in the development and early progression of rheumatoid arthritis. (March 2019) - Réthi, B; Krishnamurthy, A; Circiumaru, A; Sakurabas, K; Joshua, V; Sun, M; Szu-Ying, C; Engström, M; Wähämaa, H; Hensvold, A; Smith, JE; Catrina, AI
Abstract : Career situation of first and presenting author: Young investigator. Introduction: CCL17 and CCL22 are chemokines that bind to the receptor CCR4, which is expressed on various immune cells as well as on neurons. CCL17 has been shown to mediate the pro-inflammatory and algesic actions of GM-CSF in murine arthritis models 1 and CCL22 could activate nociceptive neurons in cell culture 2 or induce hyperthermia by acting on the hypothalamus. 3 Our previous studies have indicated that chemokine production by osteoclasts (OCs) might contribute to bone damage and arthralgia in the presence of anti-citrullinated protein antibodies. 4 5 Objectives: We analyzed the expression and potential roles of CCL17 and CCL22 during rheumatoid arthritis (RA). Methods: We compared CCL17 and CCL22 levels in the sera of individuals at risk of developing RA, in patients at early stages of RA and in healthy controls. We also studied the production of these molecules in OC cultures. We analyzed whether CCL22 can induce arthralgia or affect OC development. Results: Serum levels of CCL22 were elevated in individuals at risk of developing RA and in early untreated RA, when compared to healthy controls. On the contrary, CCL17 levels showed no significant difference between the studied cohorts. In the group of RA patients, higher CCL22 concentrations were associated with smoking. In OC cultures CCL22 production was triggered by M-CSF or GM-CSF and CCL22 levels correlated with both of these cytokines in the synovial fluid of RA patients. CCL22 induced arthralgia when injected into the ankle joints of mice and it stimulated OC differentiation in cell culture. Conclusions: The early increase of CCL22 might contribute to the development of RA, potentially by inducing pain and osteoclastogenesis. Inflammatory cytokines, like GM-CSF and M-CSF, and also by environmental triggers such as smoking can contribute to the increase of CCL22. References: Achuthan A, et al. J Clin Invest 2016. Oh SB, et al. J Neurosci 2001. Osborn O, et al. Cytokine 2011. Krishnamurthy A, et al. Ann Rheum Dis 2016. Wigerblad G, et al. Ann Rheum Dis 2016. Disclosure of Interest: B. Réthi: None declared, A. Krishnamurthy: None declared, A. Circiumaru: None declared, K. Sakurabas: None declared, V. Joshua: None declared, M. Sun: None declared, C. Szu-Ying: None declared, M. Engström: None declared, H. Wähämaa: None declared, A. Hensvold: None declared, J. Smith Employee of: GSK, A. Catrina: None declared.